2022
DOI: 10.1515/cdbme-2022-1144
|View full text |Cite
|
Sign up to set email alerts
|

On Gait Stability: Correlations between Lyapunov Exponent and Stride Time Variability

Abstract: Lyapunov exponent is a promising parameter to ascertain the stability of the human gait. In this work, we use a time-series model based on a second-order delay-system with inertial measurement units placed on the foot and wrist. Stability is analyzed in a localized sense, with the Lyapunov exponent computed in the temporal region between two heel-strike points, which are determined using a peak-detection algorithm. We have attempted to show correlations between variations in the stride time and stability of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“… Warlop et al (2016) found that the variation in the duration of strides affects the stability of gait in patients with Parkinson’s disease. Chandrasekaran et al (2022) used the Lyapunov exponent to analyze the stride intervals, found that it was correlated with variations in the duration of strides, and used this to obtain the threshold of gait stability. Aziz and Arif (2006) claimed that the stride interval of the gait reflects a law of the human gait, and analyzed the complex stability of gait in patients with neurodegenerative diseases based on the symbolic entropy of the stride interval.…”
Section: Introductionmentioning
confidence: 99%
“… Warlop et al (2016) found that the variation in the duration of strides affects the stability of gait in patients with Parkinson’s disease. Chandrasekaran et al (2022) used the Lyapunov exponent to analyze the stride intervals, found that it was correlated with variations in the duration of strides, and used this to obtain the threshold of gait stability. Aziz and Arif (2006) claimed that the stride interval of the gait reflects a law of the human gait, and analyzed the complex stability of gait in patients with neurodegenerative diseases based on the symbolic entropy of the stride interval.…”
Section: Introductionmentioning
confidence: 99%
“…To address these gaps, this study employs nonlinear dynamics methods, including the Maximum Lyapunov Exponent (MLE), Sample Entropy (SaEn), and Detrended Fluctuation Analysis (DFA), to quantitatively analyze the relationship between gait pattern characteristics and dynamic stability. These methods offer a holistic perspective on gait behavior, capturing intricate dynamics throughout the entire gait cycle [10,[17][18][19][20][21][22]. Unlike previous studies focusing on individual variables, the utilization of nonlinear dynamics tools allows us to delve into the complex interactions that shape gait stability during sudden speed changes [23,24].…”
Section: Introductionmentioning
confidence: 99%